Zur Hierarchisierung der wissenschaftlichen Assertionen mit metatextuellen Äußerungen - Olszewska, Danuta (Glottodidactica, 2001)
The article presents the ways of ranking assertions or sequences of assercions in a scientific text, with the use of metatext explications. This ranking results from introducing into the text meta-phrases which explicitly or implicitly expresses the author's speech act. Speech acts signal on the one hand the assertions which are especially important, in opposition to the important ones, on the other, second-rate assertions opposing the primary ones. The article aims to present the analysis of the text creating function of hierarchical metaphrases and the ways of realizing them.